Gender matters in global politics : a feminist introduction to international relations - Shepherd, Laura J. (Routledge, 2015)
"Gender Matters in Global Politics 2nd edition is a comprehensive textbook for advanced undergraduates studying feminism & international relations, gender and global politics and similar courses. It provides students with an accessible but in-depth account of the most significant theories, methodologies, debates and issues"--Provided by publisher